Infecciones respiratorias altas y su incidencia en neumonía en niños, de 1 a 5 años que asisten al centro de salud enrique Ponce Luque, Cantón Babahoyo, periodo septiembre 2017 a febrero 2018. - Arias Burgos, Cinthya Abigail (2018)
Acute respiratory infections are one of the first 5 causes of infant mortality, and these are defined as the set of communicable diseases of the respiratory system that includes from the common cold to pneumonia causing serious sequelae in children Because they are present throughout the year either by multiple factors including environmental pollution, type of climate among others. This investigative study is focused and aimed primarily at determining the incidence of upper respiratory infections and that attack the presence of pneumonia in children under 5 years. In order to eradicate the high morbidity rate of the children targeted by this research. The feasibility of this project will give us a contingency route to find a solution to this public social problem, which will have a positive impact on the improvement of the quality of life of children from the spatial delimitation to which This research is mentioned.